Development of Multifunctional Film for Greenhouse Applications in Tropical Regions - A. Petchsuk; D. Srinun; S. Buchatip; W. Supmak; D. Sirikittikul (Advances in Materials Science and Engineering)
Single-purpose greenhouse films such as UV-blocking, NIR-blocking, or ultrathermic films are commonly developed in various climate regions. However, multifunctional films of combined functions are rarely explored, especially in the tropical regions. In this research, a multifunctional film having high UV filtration, high NIR reflection, and good light diffusion was developed for a greenhouse cover application in tropical regions. Effects of type, quantity, and particle size of additives on optical properties (280–2500 nm) and mechanical properties of 3-layer laminated films comprising 90% LLDPE/10% EVA polymer matrix and additives were studied. Results show that properties of those films are adjustable by varying types, particle size, and content of additives. The UV transmission of the film was ranged from 13.7 to 32.7 %T, NIR reflection from 12.1 to 19.8 %R, and %haze diffusion from 39.5 to 72.3 where photosynthetically active radiation (PAR) transmission was in the range of 62.6–78.9 %T. Those films exhibit tensile strength of 18–24 MPa, modulus of elasticity of 200–280 MPa, and elongation at break of 610–810%. A field test of the newly developed films as a cover for a greenhouse of 6 m wide ×24 m long ×4.3 m high with double roof design showed a better quality of plant growth in terms of weight, height, and bush width compared to a 7% UV absorber commercial film.